Psychological and Pain Sensitization Characteristics Are Associated With Patellofemoral Osteoarthritis Symptoms: The Multicenter Osteoarthritis Study - Collins, Natalie J.; Neogi, Tuhina; Vicenzino, Bill; Guermazi, Ali; Roemer, Frank; Lewis, Cora E.; Torner, James C.; Nevitt, Michael C.; Stefanik, Joshua J. (Journal of Rheumatology, 2020)
OBJECTIVE: Determine the relation of symptomatic and structural features of patellofemoral osteoarthritis (PFOA) to psychological characteristics and measures of pain sensitization, in older adults with or at risk of knee osteoarthritis (OA). METHODS: This study included 1112 participants from the Multicenter Osteoarthritis Study (713 females, mean age 66.8 ± SD 7.6 yrs, body mass index 29.5 ± 4.8 kg/m2). Participants were grouped based on the presence of PFOA symptoms (anterior knee pain and pain on stairs) and magnetic resonance imaging (MRI) PFOA (full-thickness cartilage lesion with bone marrow lesion): (1) patellofemoral (PF) symptoms with MRI PFOA; (2) PF symptoms without MRI PFOA; (3) MRI PFOA without PF symptoms; and (4) no PF symptoms or MRI PFOA (no PFOA). Relation of PFOA classification to depressive symptoms, catastrophizing, temporal summation (TS) and pressure pain thresholds (PPT) was evaluated using logistic (categorical variables) and linear regression (continuous variables). RESULTS: Compared with no PFOA, those with PF symptoms with or without MRI PFOA had significantly greater odds of depressive symptoms, catastrophizing, and patellar TS (OR range 1.5-2.01), and those with PF symptoms without MRI PFOA had significantly greater odds of wrist TS (OR 1.66). Males with PF symptoms without MRI PFOA had significantly lower pressure PPT at the patella compared with no PFOA and those with MRI PFOA only (no symptoms). There were no significant differences at the wrist for males, or the patella or wrist for females. CONCLUSION: Persons with PFOA symptoms, regardless of MRI PFOA status, are more likely to demonstrate depressive symptoms, catastrophizing, and TS. Males with PFOA symptoms without MRI PFOA demonstrate local hyperalgesia.
CRIS-Team Scopus Importer:2020-11-13
Keywords: knee; magnetic resonance imaging; osteoarthritis; pain